1976
DOI: 10.1159/000212123
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between DNA Repair Capacity and Cellular Aging

Abstract: The experimental evidence is reviewed which bears on the theory that aging in mammalian cells may be related to a decline in the efficiency of normal DNA repair processes. Although the data are as yet fragmentary, they do suggest that there is an age-associated decline in the capacity of cells to perform at least certain types of repair. This is particularly noticeable in human diploid cells as they reach terminal senescence in vitro. Whether this decline is causally related or even contributory to normal agin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

1978
1978
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Experiments in human diploid fibroblasts and additional cell types document an inverse correlation between replicative senescence and donor age and a direct relationship between replicative senescence and donor-species life span (13,19,20). In agreement with this relationship, cells from patients with premature aging syndromes such as Werner's syndrome and progeria achieve a quiescent state more rapidly than normal human fibroblasts (21). Although senescence is a time-dependent process, terminal differentiation can be induced in a variety of cell types by appropriate treatment (2,3,16).…”
mentioning
confidence: 68%
“…Experiments in human diploid fibroblasts and additional cell types document an inverse correlation between replicative senescence and donor age and a direct relationship between replicative senescence and donor-species life span (13,19,20). In agreement with this relationship, cells from patients with premature aging syndromes such as Werner's syndrome and progeria achieve a quiescent state more rapidly than normal human fibroblasts (21). Although senescence is a time-dependent process, terminal differentiation can be induced in a variety of cell types by appropriate treatment (2,3,16).…”
mentioning
confidence: 68%
“…Given that DNA is both intrinsically unstable and subject to continuous modifications from reactive oxygen species and other environmental factors, the genomic integrity of the cell throughout life is dependent on protective DNA repair mechanisms. It has long been reported that there is a general age‐dependent decline in the efficiency of normal DNA repair processes , whereas an aging‐related increase in oxidative damage to DNA was also shown in different tissues . In HSCs, it has been shown that endogenous DNA damage accumulates with age, affecting SC functionality .…”
Section: Dna Damage and Repairmentioning
confidence: 99%
“…This difference in cytotoxicity implied that the target size of the CS' cells could be larger than that of the CS-cells or that repair may be more efficient in the CScells. Repair capacity has been reported to decline with both in vitro senescence (15) and cellular differentiation (16). Induction of morphological transformation was dose-dependent.…”
mentioning
confidence: 99%